PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Tita Anggraeni, 14.05.52.0041; Parnono Hadi, Teguh (Students' Journal of Accounting and Banking, 2018)
The purposes of this research are to analyze the influence of Institutional Ownership variable, Managerial Ownership, and Capital Structure on the value of the company. The assessment of this hypothesis is based on the Multiple Regression. The total samples used in this research are 254 manufacture companies registered in Indonesia Stock Exchange (BEI) with purposive sampling method. Purposive sampling method is a determined method technique based on Criteria. What means by Criteria in this research is manufacture companies registered in Indonesia Stock Exchange in the period of 2013 until 2016. The result of this result shows that Institutional Ownership and Managerial Ownership havea significant negative effect on the value of the company. In the other hand, Capital Structure has an insignificant positive effect on the value of the company. Key words: Institutional Ownership, Managerial Ownership, Capital Structure and Value of company